EFL University Students’ Difficulties and Strategies in Taking the EnglishScore Test - Ayu Lestari; Ameera Fadhillah; Priska Oktaviani Br Ginting; Lia Lisyati (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2026)
This study aimed to identify the difficulties experienced by EFL English Language and Literature students in taking the EnglishScore test and to explore the strategies they used to overcome those difficulties. This study employed a descriptive qualitative research design involving 45 students from the English Language and Literature Department who had previously taken the EnglishScore test. The data were collected through an open-ended questionnaire distributed online. The collected data were analyzed using thematic analysis by categorizing students’ difficulties based on Chapelle and Douglas’ theory of digital language assessment and students’ strategies based on Oxford’s Language Learning Strategies theory. The findings revealed that listening comprehension difficulties became the most dominant difficulty with a frequency of 29 responses, particularly related to fast speech and unfamiliar accents. Meanwhile, cognitive strategies became the most frequently used strategies with 26 responses, especially practicing listening exercises and identifying keywords. Overall, the findings showed that students relied on various learning strategies to complete the EnglishScore test more effectively.